GENETIC DIVERSITY ANALYSIS OF KAIL SHEEP BY USING MICROSATELLITE MARKERS - Z. Ahmed; M. E. Babar; T. Hussain; A. Nadeem; F. I. Awan; A. Wajid; S. A. Shah; M. M. Ali (Journal of Animal and Plant Sciences, 2014)
The Kail sheep breed of Azad Jammu and Kashmir (AJ&K) was analyzed by using 11 microsatellite markers in order to estimate genetic diversity of this famous breed. This study aimed to provide information on the genetic structure of the Kail breed. In total 47 samples of Kail sheep were genotyped. We obtained 58 alleles, while average number of alleles was 5.2727 ranging from 3 (INRA32, MM12) to 8 (MAF70). The observed heterozygosity (Ho) and expected heterozygosity (He) values were 0.7659 and 0.7185 respectively, most likely as a result of the mating structure of the Kail sheep breed. High heterozygosity values in the investigated population revealed low level of inbreeding, low selection pressure.  Within population inbreeding estimates (FIS = 0.0525) further supported low rate of inbreeding. The mean polymorphism information content (PIC) value was 0.60, indicating that the set of used markers were highly informative and may be used in parentage identification. This is the first report of microsatellites based variation in Kail sheep breed and it may assist to construe the genetic characteristics and benefit to the future conservation programs.
Keywords: Kail sheep; Azad Jammu and Kashmir; Microsatellite markers; Genetic Diversity